STRATEGI GURU PAI DALAM MENGATASI KESULITAN MEMBACA AL-QURAN PADA SISWA KELAS V SD NEGERI 17 PIMPINAN PARIT KECAMATAN TELUK KERAMAT TAHUN PELAJARAN 2023/2024 - Dwita Amanda; Rusiadi; Muhammad Asyura (CV. ADIBA AISHA AMIRA, 2025)
This study discusses the strategies used by Islamic Education teachers in overcoming difficulties in reading the Quran among fifth-grade students. This study has three objectives, including the following: first, to analyse the planning of Islamic Education teachers in overcoming difficulties in reading the Quran among fifth-grade students at State Elementary School 17 Pimpinan Parit. Second, to analyse the implementation of PAI teachers' strategies in overcoming difficulties in reading the Quran among fifth-grade students at State Elementary School 17 Pimpinan Parit. Third, to analyse the implications of the use of PAI teachers' strategies in overcoming difficulties in reading the Quran among fifth-grade students at State Elementary School 17 Pimpinan Parit. Information obtained from Islamic Education (PAI) teachers at State Elementary School 17 Pimpinan Parit indicates that they have strategies that can help students who experience difficulties in reading the Quran. According to these teachers, most students still experience difficulties in reading the Quran. This is based on an interview with the Islamic Education Teacher (PAI) Habibah S.Pd.I, who said that previously many students still had difficulty reading the Quran due to a lack of guidance and encouragement from their parents at home to teach their children to read the Quran. Furthermore, the teacher revealed that the lack of guidance and supervision from parents regarding the development of their children's ability to read the Quran is one of the causes of their inability to read the Quran. In addition, there are other factors that underlie the students' difficulty in reading the Quran, such as the lack of Islamic Education (PAI) lessons at school and environmental factors, where their friends often invite them to play games, causing the students to be lazy to learn to read the Quran.